The emerging roles of piezo1 channels in animal models of multiple sclerosis - Yang, Kai; He, Xueai; Wu, Zhengqi; Yin, Yimeng; Pan, Hanyu; Zhao, Xinyue; Sun, Taolei (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is the most common chronic inflammatory, demyelinating, and neurodegenerative disease in the central nervous system (CNS). Its pathogenesis is quite complex: Accumulated evidence suggests that biochemical signals as well as mechanical stimuli play important roles in MS. In both patients with and animal models of MS, brain viscoelasticity is reduced during disease progression. Piezo channels are recently discovered mechanosensitive channels, and their three-dimensional structure has been solved. Both the membrane dome mechanism and the membrane footprint hypothesis have been proposed to explain their mechanosensitivity. While membrane-mediated forces alone appear to be sufficient to induce Piezo gating, tethers attached to the membrane or to the channel itself also seem to play a role. Current research indicates that Piezo1 channels play a key role in multiple aspects of MS pathogenesis. The activation of Piezo1 is required for demyelination; in addition, the inhibition of Piezo1 in CD4+ T cells and/or T regulatory cells (Treg) attenuates experimental autoimmune encephalitis (EAE) symptoms. Although more work has to be done to clarify the roles of Piezo1 channels in MS, they might be a promising future drug target for MS treatment.